Feminism and translation : a case study of two translations of Mariama Bâ : une si longue lettre (so long a letter) and un chant écarlate (scarlet song) - Morgan, Naomi (University of Pretoria, 2015)
Mini Dissertation (MA)--University of Pretoria, 2015.